Methodological bases of management of business activity of enterprises in the conditions of globalization - Ptashchenko, Olena; Shersheniuk, Elena; Птащенко, Олена Валеріївна; Шершенюк, Олена Миколаївна (Харківський національний автомобільно-дорожній університет, 2023)
Summary. The main aspects of managing the business activity of enterprises in the conditions of globalization are considered in the presented work. The development of market relations, which is characterized by the complication of business processes, an increase in the required level of scientific knowledge of manufactured products, a reduction in the life cycle of goods and the development of information, leads to awareness of the importance and necessity of introducing innovations and ensuring innovative activity. With the help of innovations, a systematic process of creation, introduction of new goods, equipment or technology (production, management, information support, etc.) or reduction of the cost of existing products is carried out, with the aim of increasing business activity and obtaining a socio-economic effect. Thus, innovations are an important functional area of business activity of enterprises. The purpose of the work is research and development of methodological foundations of management of economic activity of enterprises in the conditions of globalization. Research methods. The main research methods are observation, forecasting, methods of analysis and synthesis, logical method. All proposed research methods are aimed at determining the main trends of modern times in the direction of managing the business activity of enterprises in order to increase their competitiveness in the conditions of globalization and changes. Results. A methodological approach to managing business activity has been developed. The analyzed methodological approaches to the analysis of business activity made it possible to classify them depending on the application of the used methods on the main functional areas of business activity of enterprises. Given that the functional areas of business activity are divided into five categories (marketcommercial, financial, investment, personnel, production), the proposed classification of business activity analysis methods takes into account the specific properties inherent in each relevant area, which constitutes the novelty of the research. Scientific novelty. In addition, the author's development improved the structuring of business activity assessment methods, which today is characterized by differences of opinion regarding its implementation, assigning this or that method to a certain functional area. The given classification contributes to the systematization of methods of analysis of business activity, allows you to choose one or more of the most appropriate methods for a certain specific situation among their large number. Practical significance. The proposed approach, based on the structuring of methods for assessing the business activity of enterprises, allows optimizing marketing and management decisions at the enterprise and increasing its competitiveness.
Методологічні основи управління діловою активністю підприємств в умовах глобалізації
Keywords: management system; business activity of the enterprise; globalization process; components of business management; indicators of business activity; система управління; ділова активність підприємства; глобалізаційний процес; складові управління діловою активністю; показники ділової активності; 339.138; 10.30977/PPB.2226-8820.2023.30.38